2001
DOI: 10.3354/meps213193
|View full text |Cite
|
Sign up to set email alerts
|

Pattern, synchrony and predictability of spawning of the tropical abalone Haliotis asinina from Heron Reef, Australia

Abstract: The spawning biology of the tropical abalone Haliotis asinina on Heron Reef, Australia, was investigated to identify putative environmental and endogenous factors controlling spawning. Spawnings by H. asinina were highly regular and, in comparison to most other haliotids and marine invertebrates, frequent and extremely synchronous. These events appeared to be regulated by more than 1 environmental cue. The spawning season of H. asinina extends from October to April and is associated with an increase in water t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 28 publications
(48 reference statements)
2
67
0
Order By: Relevance
“…In H. laevigata and H. cyclobates, the period of maximum gonad growth coincided with that of an abundant food supply (Shepherd and Law, 1974) and optimal feeding possibilities (Shepherd, 1973). More recently, Counihan et al (2001) suggested that the spawning of H. asinina in the Heron Reef, Australia, was associated with an increase in water temperature (October to April), and that other environmental cues, such as the tidal regime, also appeared to play a role.…”
Section: Spawning Seasonmentioning
confidence: 98%
See 1 more Smart Citation
“…In H. laevigata and H. cyclobates, the period of maximum gonad growth coincided with that of an abundant food supply (Shepherd and Law, 1974) and optimal feeding possibilities (Shepherd, 1973). More recently, Counihan et al (2001) suggested that the spawning of H. asinina in the Heron Reef, Australia, was associated with an increase in water temperature (October to April), and that other environmental cues, such as the tidal regime, also appeared to play a role.…”
Section: Spawning Seasonmentioning
confidence: 98%
“…The reproductive seasonality of many abalone species from various regions in the world has been studied previously (Boolootian et al, 1962;Tomita, 1967Tomita, , 1968Newman, 1967;Webber and Giese, 1969;Poore, 1970;Young and de Martini, 1970;Tutschulte and Connell, 1981;Capinpin et al, 1998;Counihan et al, 2001). Harrison and Grant (1971).…”
Section: Introductionmentioning
confidence: 99%
“…Haliotis discus hannai larvae are detected primarily after typhoons or minor storms 33 while H. kamtschatkana and H. rubra are suggested to spawn during calm periods 2,30 . Tanaka 43 concluded that sudden temperature changes induced the spawning of H. discus discus, H. madaka and H. gigantea, while the spawning of H. asinina appears to be triggered by the lunar cycle and/or tidal amplitude 4 . From our results, the spawning of H. diversicolor in Sagami Bay is strongly associated with typhoon events 24 .…”
Section: Spawningmentioning
confidence: 99%
“…In this regard, it is important to review, test and define the available options for estimating MI. In haliotids, these indices have been used primarily to evaluate the reproductive status of populations (Boolootian et al, 1962;Webber and Giese, 1969;Poore, 1973;Ault, 1985;Capinpin et al, 1998;Counihan et al, 2001;Litaay and De Silva, 2002;Najmudeen and Victor, 2004;Setyono, 2006). The simplest indicator is calculated by dividing the gonad weight by the total weight of the body, and it is commonly used in haliotids (Setyono, 2006) and other gastropods (Zetina et al, 2000;Morais et al, 2003;Abidli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%